Decision Support System Recommendations of Half and Full Subsidized KPR Houses - rizalul akram; Novianda Novianda; Sri Wulandari (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2020)
The house is a primary need for humans because as a place to stay and carry on life. Having a house is certainly not an easy matter because it requires a very large cost for it. This large amount of capital has made the community take a short and practical path by choosing half or full subsidized housing loans. Only with a capital of 20 million housing mortgages can be placed. However, the case of the house also considers the size, area, model, size of the remaining land, and location to be crucial in the selection. At present the types of KPR houses consist of types 36, 45, and 54. All three types have subsidies from the government so that they are affordable by many communities. However, from the results of field observations many people felt that it was not appropriate to choose the type of house. Let's say someone wants a type 45 house but ends up choosing type 36 with an estimated objection to paying monthly installments, even though they are capable. And vice versa who take type 45 then object to paying the monthly installments. Based on these problems, the authors try to help the community through the bank with the application of a decision support system (SPK). With this system, people who have filled out the registration form on the system will get a recommendation for the type of house. This system was built using the simple addative weight (SAW) method.Keywords: House, KPR, Type, SPK, SAW.